Social Class Predicts Generalized Trust But Only in Wealthy Societies - Hamamura, Takeshi (Sage Publications, 2012)
This research examined the relationship between social class and generalized trust, or a belief that others have a benign intention in social interactions, in a diverse set of societies represented in the World Values Survey. The strength of the relationship varied significantly across societies: Although social class was a positive predictor of generalized trust in wealthy countries, as reported in past research, among less wealthy countries social class was uncorrelated with trust. These results indicate that resources available to individuals of high social class may make a trusting belief more rewarding; nevertheless, in less wealthy societies, the socio-political economic infrastructure that supports generalized trust is unavailable, and therefore even individuals of high social class are reluctant to trust others. This finding extends prior theorizing on trust in finding the interactive relationship between an individual-level factor and a society level factor in shaping individuals’ inclination toward trust.